THE INTEGRATION OF ARTIFICIAL INTELLIGENCE (AI) INTO EDUCATION SYSTEM (TAMADDUN NURI JURNALI, 2024)
As research on artificial intelligence (AI) in education continues to expand, many scholars predict significant changes in the roles of teachers, schools, and educational leaders. This study seeks to examine potential outcomes of integrating AI into education and its implications for the future of educational institutions. Using a phenomenological approach, a qualitative research method, the study explores the perspectives of individuals from diverse sectors. The findings indicate that AI's introduction in education will bring innovative tools and advantages for schools and teachers, while also presenting certain challenges.